Zn(ii)-Coordination-driven self-assembled nanoagents for multimodal imaging-guided photothermal/gene synergistic therapy. Issue 24 (10th June 2022) - Hu, Hui; Yang, Nan; Sun, Jiahui; Zhou, Fu; Gu, Rui; Liu, Yuan; Wang, Li; Song, Xuejiao; Yun, Ruirui; Dong, Xiaochen; Wang, Guangfeng
Abstract : siRNA@PT-ZIF-8 was prepared by one pot self-assembly for tri-mode imaging guided mild-temperature photothermal synergetic gene therapy. Abstract : Synergistic photothermal therapy (PTT) with gene therapy (GT) has drawn emerging interest in the improvement of cancer therapeutic efficiency, while the co-delivery of photothermal agents (PTAs) and therapeutic genes by an integrated nanoplatform, with controllability and biodegradability, is still challenging and urgently desired. Herein, a multi-functional metal–organic framework (MOF) based PTT–GT platform (siRNA@PT-ZIF-8) was developed, which was constructed with siRNA, a near-infrared (NIR) responsive organic dye IR780 derivative (IR780-1), and 2-methylimidazole (2-MIM) by a facile one-pot self-assembly method. This "all-in-one" system of siRNA@PT-ZIF-8 enabled not only photothermal/photoacoustic/fluorescence multimodal imaging but also tumor microenvironment responsiveness for specific and on-demand release of therapeutic cargos, overcoming the inherent limitations of free gene or organic PTA molecules ( e.g., short blood circulation half-life and weak stability) in conventional PTT and GT. This nanoplatform provides an efficient and safe strategy for cancer theranostics, and the one-step assembly strategy favors personalized formulation design for diverse demands in cancer management.